EFL Students’ Perception of Using TikTok to Improve English Speaking Skills - Juwita, Intan; Faizah, Cut (Universitas Serambi Mekkah, 2024)
English speaking is one of the language skills that must be mastered by university students. TikTok is one of the media for learning English, namely speaking and listening. In the study, the researchers emphasized the speaking aspect. The purpose of this research is to find out students’ perceptions about using TikTok to improve their English speaking skills. The study used a quantitative design. The samples in this research were USM andUNMUHA students in Banda Aceh, where this research aims to obtain information that is on the knowledge and experience possessed by these students. To collect the data, researchers distributed a questionnaire. The data obtained from questionnaire data collection showed that the participants' speaking skills had improved, namely the TikTok application helps improve their speaking wherever students are as long as connected to be internet and 90.